Heterogeneity among Venezuelan migrants in terms of coping in the context of the population exodus from Venezuela - Marcin Stonawski (PLoS ONE, 2025)
This study concentrates on the unparalleled exodus of Venezuelans in recent years. By June 2024, the global population of Venezuelan migrants and refugees had reached 7.7 million, with 6.6 million settling in Latin America. This represents one of the most significant migration outflows of the 21st century, with estimated numbers exceeding those of emigration from Afghanistan, Ukraine and Syria. However, coping strategies and integration of Venezuelans in hosting countries is understudied phenomenon in comparison to other migration movements. The aim of this paper is to examine patterns of coping among Venezuelan migrants. By analyzing coping strategies, we aim to contribute to enhance understanding of the characteristics of Venezuelan migrants in the context of their adaptation in the host countries in Latin America. We conducted a survey among Venezuelan migrants in Peru in 2023. The study is based on the Lazarus and Folkman model of stress and coping. A Coping Strategy Inventory-SF instrument and a Latent Class Analysis method were employed to distinguish three homogeneous subgroups in terms of coping strategies. We found three such subgroups: problem engagers, hybrid engagers and mixed strategy users. These groups exhibit distinct characteristics with regards to age, sex, education and optimism. The article highlights the heterogeneity in the use of coping strategies among Venezuelan migrants. To the best of our knowledge, this study is the first one to apply Lazarus and Folkman’s model in conjunction with Latent Class Analysis in the field of migration studies. We strongly believe the proposed approach is useful in increasing our understanding about coping strategies and integration among migrant populations.